Decay Tree Detection in Bogor Botanic Gardens Collection Using Sonic Tomograph Technology - Zulkarnaen, Rizmoon Nurul; Rinandio, Dipta Sumeru; Hariri, Muhammad Rifqi; Hutabarat, Prima Wahyu Kusuma; Martiansyah, Irfan; Wardani, Fitri Fatma; Mujahidin, Mujahidin; Primananda, Enggal; Rachmadiyanto, Arief Noor; Mulyani, Melza; Husaini, Iin P.A; Setyanti, Dwi; Indresputra, Faozan; Rahmaningtiyas, Lutfi; Pratiwi, widya Ayu; Damayanti, Frisca; Endewip, Lidya N.; Helmanto, Hendra; Suhatman, Agus; Safarinanugraha, Dina; Purnomo, Danang Wahyu (Fakultas Sains dan Teknologi, UIN Walisongo Semarang, 2022)
Bogor Botanic Gardens is an ex-situ plant conservation area in Indonesia. Since BBG is 103 years old, many collections are 100 years old or older. These antique collections may sustain damage, such as broken or collapsing, endangering visitors and employees. As a result, monitoring tree health at BBG is a critical task. According to the tree health monitoring data, 73 of 244 trees were further checked using the PiCUS Sonic Tomograph. Trees from the Fabaceae (31%) and Myrtaceae (10%) families were the most frequently checked. Walnuts trees from the Burseraceae family had the most specimens (47,94%). The PST effectively provides an immediate picture of the stem condition by calculating solid and decaying wood percentage values.